2012
DOI: 10.1039/c2an35329f
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination of functional hepatocytes derived from mesenchymal stem cells using FTIR microspectroscopy

Abstract: Functional hepatocytes differentiated in vitro from mesenchymal stem cells (MSCs) need to be fully characterized before they could be applied as a therapy to treat liver disease. Here, we employed Fourier Transform Infrared (FTIR) microspectroscopy to investigate the characteristics of hepatocyte-like cells derived from rat bone marrow mesenchymal stem cells (rBM-MSCs) by detecting changes in macromolecular composition occurring during the hepatogenesis process. Partial Least Squares Discriminant Analysis (PLS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 48 publications
(42 reference statements)
1
16
0
Order By: Relevance
“…Spectral changes related to proteins clearly suggested that differentiated glioma stem cells express a different set of genes/proteins compared to control stem cells, although the specific proteins remain unidentified. Similar conclusions were drawn by Ye et al [25], where they observed several changes in protein secondary structure at different levels of differentiation of mesenchymal stem cells. In addition, both PC4 loading and the difference spectrum showed a decrease of the spectral band centered at 965 cm −1 , assigned to the symmetric stretching mode of di-anionic phosphate mono-esters of phosphorylated proteins [26] and therefore pointing to a decrease in the level of phosphorylated proteins in the differentiated glioma cells.…”
Section: Ftir Microspectroscopy Measurements Reveal Changes In Lipidssupporting
confidence: 78%
“…Spectral changes related to proteins clearly suggested that differentiated glioma stem cells express a different set of genes/proteins compared to control stem cells, although the specific proteins remain unidentified. Similar conclusions were drawn by Ye et al [25], where they observed several changes in protein secondary structure at different levels of differentiation of mesenchymal stem cells. In addition, both PC4 loading and the difference spectrum showed a decrease of the spectral band centered at 965 cm −1 , assigned to the symmetric stretching mode of di-anionic phosphate mono-esters of phosphorylated proteins [26] and therefore pointing to a decrease in the level of phosphorylated proteins in the differentiated glioma cells.…”
Section: Ftir Microspectroscopy Measurements Reveal Changes In Lipidssupporting
confidence: 78%
“…[27] aligned with non-spectroscopic studies which report that hepatocytes routinely synthesise lipoproteins and synthesise and store triglycerides as a result of activities from carbohydrate metabolic pathways. Moreover, a significant increase in unsaturated fatty acid levels was seen in the late stage hepatocytes, indicated by an increase in the intensity of C–H stretching band associated with the cis double bond C=C at 3010 cm −1 .…”
Section: Multipotent Stem Cell Applicationsmentioning
confidence: 99%
“…The spectroscopic technique has also been adopted for studies of rat bone marrow mesenchymal stem cells (rBM-MSCs) differentiated to hepatocytes [27]. The main findings from the work were that the late stage differentiated cells possessed significantly higher levels of lipid compared to the stem cell progenitors and early stage differentiated cells, with notable differences in the FTIR absorbance bands at: 3012 cm −1 (cis C=C stretch from unsaturated lipids), 2952 cm −1 (ν as CH 3 from lipids), 2854 cm −1 (ν s CH 2 from lipids) and 1722 cm −1 (C=O stretching from lipids).…”
Section: Multipotent Stem Cell Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most characterization approaches rely on sample manipulation to gain information beyond morphology and are incapable of analyzing intact 3D cell aggregates that are known to be crucial for the maintenance of stem cell state [82]. Recently, 2D vibrational spectroscopy has been applied to study stem cells and several reports have noted a significant spectroscopic change in bands associated pluripotent versus multipotent cells [83,84] and between multipotent cells and derived hepatocytes [85]. The utility of vibrational spectroscopy in the future would benefit greatly from the 3D spectral microtomography technique and associated preservation of crucial cell–cell and cell–extracellular matrix interactions.…”
Section: Examplesmentioning
confidence: 99%